Damage characteristics and distribution patterns of invasive pest, Spodoptera frugiperda (J.E Smith) (Lepidoptera: Noctuidae) on maize crop in Bali, Indonesia - I WAYAN Supartha; I WAYAN SUSILA; ANAK AGUNG AYU AGUNG SRI SUNARI; I. G. FEBRI MAHAPUTRA; I KADEK WISMA YUDHA; PUTU ANGGA WIRADANA (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Supartha IW, Susila IW, Sunari AAAAS, Mahaputra IGF, Yudha IKW, Wiradana PA. 2021. Damage characteristics and distribution patterns of invasive pest, Spodoptera frugiperda (J.E Smith) (Lepidoptera: Noctuidae) on maize crop in Bali, Indonesia. Biodiversitas 22: 3378-3387. The Fall Armyworm (FAW), Spodoptera frugiperda (Lepidoptera: Noctuidae) is a destructive crop pest native to North and South America which has now been reported to have spread to Indonesia. This study aims to ensure the attack and spread of invasive pests FAW on corn crops in Bali. In addition, it also studied population structure, age structure, and percentage of attacks on maize crops in high altitude areas in Bali, Indonesia. The research was conducted using survey methods. A sampling of plants is carried out in all districts and cities in the Province of Bali by diagonal sampling. The sample unit size is 5 m × 5 m with the number of plants observed being 150 plants. The score of plant damage at the age of 4 weeks after planting (WAP) plants has a "very heavy" attack intensity value. Areas of upper leaves or young leaves most affected by S. frugiperda attack in the field. The results showed that pest FAW has been entering and attacking maize crops in Bali since January 2020 as the first report. At the beginning of the entry was only found in some lowland locations, especially in Tabanan and Jembrana regency, but within the next 4 months, it has spread evenly in all districts and cities in Bali province. Adults populations and egg groups of FAW were found to peak by the time the corn crop was 2 weeks old after planting while the larval population reached its peak by the time the plant was 4 WAP The highest percentage of FAW attacks is in altitude areas below 250 meters above sea level (masl) with an average attack per observation plot of 47.84%. This research is the first to report on FAW attacks on maize crops in Bali Province since January 2020 and adds to our knowledge of FAW pests on maize crops in Bali Province.